THE EFFECT OF GUIDED WRITING ON STUDENTS' WRITING SKILLS - Eneng Liah Khoiriyah; Rasikin Rasikin (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2021)
The purpose of this research is to explain whether the effect of guided writing can improve the students’ writing skill. The writer conducted in quasi experiment in this research. There are involving two classes for the research, namely experiment class and control class. The experiment class used guided writing as the technique and the control class without using guided writing. Before starting the treatment, the writer giving pre-test to know how far the students’ ability in writing text. After the writer giving the pre-test, the writer give the treatment to the experimental class, in the case the eighth grade students in class 8. The writer applied the technique or treatment of using guided writing. The next meeting the writer gave post-test to find out whether there was significance effect using guided writing technique toward the writing skill students. the result of the study, the researcher drew two conclusions. The first conclusion is that guided writing can significantly improve the students’ writing skill. In this case, the students could correctly construct sentences based on the grammar explained by the researcher. In general, students are encouraged to practice writing as much as possible. The second point to be concluded is that the implementation of guided writing has improved the students motivation in learning writing.